(untitled) (Italian Journal of Public Health, 2003)
Occupational exposure to benzene in petrol pump attendants and in mechanics was studied by examining the benzene content in both the air breathed and in the urinary metabolite trans,trans-muconic acid (t,t-MA). Thirty petrol pump attendants and thirty mechanics (as exposed workers) and thirty adult male office workers (as non exposed workers) were involved in the study. Measures were taken at the begin and at the end of the working shifts. The benzene concentrations in the breathing air samples varied from 2 to 88 μg m-3, lower than the EU acceptable limit for occupational environment. The average urinary t,t-MA in the petrol pump attendants at the begin and at the end of the working shifts ranged between 133 ± 69 and 255 ± 174 μg g-1 creatinine and in the mechanics between 204 ± 139 and 300 ± 211 μg g-1 creatinine, respectively. In all the participants the mean levels of urinary t,t-MA at the end of the working shifts were significantly higher than those at the beginning. In the exposed workers mean levels of urinary t,t-MA were significantly higher than in those of the non-exposed workers. The influence of the smoking was demonstrated by the urinary t,t-MA levels in smoking non-exposed subjects.